Risk Management Implementation Strategy And Bank Health Level Assessment In The Framework Of Increasing The Performance of PT. BPR Jatim - Tjahjono, Tjahjono; Budiyanto, Budiyanto; Khuzaini, Khuzaini (International Journal of Science, Technology & Management, 2023)
BPR JATIM is one of the pilots BPR in the East Java operational area that has good risk management, and has just won the 2nd Best Indonesian Enterprises Risk Management Category: Local Government with assets of over IDR 1 trillion from Economic Review Magazine. This makes PT. BPR JATIM is recognized as one of the best BPRs with good risk management implementation. Therefore, this research was conducted to analyze the quality of risk management implemented by PT. BPR JATIM and to determine the health level of PT. BPR JATIM. Qualitative research with a case study approach is used in this research. Instrumental provisions of Regulation Number 13/POJK.03/2015 and SE OJK No.1/SEOJK.03/2019 concerning Implementation of Risk Management, as well as SK DIR BI No.30/12/KEP/DIR/1997, are used to analyze the implementation of management risks and the bank's ability to improve and maintain its soundness from a financial perspective. The results of this study indicate that PT. It turns out that BPR JATIM has implemented good risk management including credit risk, operational risk, compliance risk, liquidity risk, reputation risk and strategic risk, where all risks have been managed properly. The results of this study also found a link between risk management at PT. BPR JATIM with its financial analysis, where good risk management has also shown a good level of bank soundness as well.